MANFAAT PENERAPAN OUTDOOR LEARNING DALAM MENINGKATKAN KECERDASAN SPASIAL - Yenni Novita Harahap; Sofia Idawati Lubis; Arianto Arianto; Lailan Syafira Putri Lubis; Ummu Atiqoh (JALIYE: Jurnal Abdimas, Loyalitas, dan Edukasi, 2023)
Education is important to be applied from an early age. Through the Educator, the concentric intelligence that a child possesses can be developed. Howard Gardner argued that there are nine types of intelligence: musical intelligence, kinesthetic, logical-mathematical, verbal-linguistic, visual-spatial, interpersonal, intra-personnel, naturalistic, and existential intelligence. At SD Muhamaddiyah 01 Field, we saw a low level of student spatial intelligence due to the fact that so far students were only shown shapes through two-dimensional pictures. Spatial intelligence or the ability to understand and organize information in spatial forms (spaces and shapes) has many benefits and relevance in everyday life. Outdoor learning, or outdoor learning, has been studied extensively and has proven to provide a variety of benefits to the learning-teaching process. Here are some backgrounds why outdoor learning can help enhance spatial intelligence: Direct interaction with the physical environment: In an outdoor environment, students have the opportunity to interact directly with a physical environment, such as a park, forest, or playground. This activity is well run. The activities carried out as a guard of activity are walking around Cadika Medan Park while singing and enjoying. Then look and observe the circumstances and pour them into a bowl using their own language.  The students were instructed to smell the leaves that sprang up on the ground in different colors and shapes. Then the students and the accompanying teachers sat together somewhere in a group way. Each group has one mentor or dedication executor. After that activity each group starts doing other activities, such as cooking, playing pompa, guessing the names of plants and animals. The last activity of this implementation each child in the group has a task to write down and tell the experiences he has gained through this activity. Most students feel happy and happy to have been given the opportunity to pursue their learning outside of school.